Plan de promoción turística, su influencia en la llegada de visitantes al cantón Mocache, Provincia de Los Ríos 2022 - Alvarado Macias, Kimberly (2022)
This research begins by describing the current tourist reality of the Mocache canton, the main objective of this promotion plan is to design the promotion and promote its tourist attractions in general, seeking to encourage and improve the tourist activity of the Mocache Canton, which made up one of the 13 Cantons that belong to the Province of Los Ríos. The implementation of a promotion plan will contribute to the growth of the Mocache canton in the social and economic sphere, causing the project to have a positive impact on the Mocache population. It is necessary to have the full support of its main authorities so that the promotion objectives set out in this project are carried out successfully and the expected results are achieved. First, the general aspects of the canton were determined, such as the geographical delimitation, climate, population, among others: in the same way, an analysis of the current situation of tourism in this sector was carried out, as well as a study of its attractions, plant and infrastructure. tourism for having a vision of the tourist situation in which the canton finds itself. And because of the afore mentioned, it was possible to design possible solutions for the planted proposal and make it valid. Today the power of tourism and the impact it has on the economic sector is known.